Kinetic modeling of enzymatic saccharification using wheat straw pretreated under autohydrolysis and organosolv process - Ruiz, Héctor A. (2012)
The enzymatic saccharification kinetics of untreated wheat straw, pretreated solids obtained by a sequence of autohydrolysis (solubilization of hemicellulose) and organosolv (solubilization of lignin) were studied together with two pure cellulose model substrates, filter paper and Avicel. Two kinetic models for glucose production were compared and its kinetic constants calculated. According to the obtained results, enzymatic saccharification of the autohydrolysis pretreated solids (APS) proved to be more effective than when the organosolv pretreated solids (OPS) were used. The maximum extent of the enzymatic conversion of cellulose to glucose was 90.88% and 64.04%, for APS and OPS respectively, at 96 h. This result was probably due to an increase in accessible area for APS and a possible inhibition by phenolic acids deposited on the surface of OPS, acting as a barrier for enzymatic saccharification. Initial saccharification rate for APS and OPS was 0.47 g/(L h) and 0.34 g/(L h), respectively. Models based on first and second order cellulase deactivation kinetics satisfactory predicted the behavior of glucose production, however the second order model had a higher accuracy than the first order one. Visualization of structural modification induced by enzymatic saccharification at 12 h for the pretreated solids was done using scanning electron microscopy.